NATIONAL IDEAS ABOUT CHILDREN'S PARK - Conceicao, Aline de Novaes [UNESP]; Filho, Macioniro Celeste [UNESP] (Fundacao Univ Tocantins, 2021)
In this article there are results of research elaborated with the objective of presenting the relationship between notional ideas about the Children's Parks of the mid-20th century with the singularities and common elements of Children's Parks in the municipality of Marilia/SP. For this, through historical approach centered on bibliographic and documentary research, the Manila's newspapers and the Revista Brasileira de Estudos Pedagogicos were used as sources-this one, one of the national supports for the debate of educational ideas. The results showed that the Children's Parks were viewed in a positive way, with the possibility of recreation. in addition, there is also the relationship with the valorization of Physical Education, games, culture, outdoor activities, formation of recreationists and the valorization of families as partners.
Keywords: Education; Education History; Recreation